Seasonal variation of tropospheric bromine monoxide over the Rann of Kutch salt marsh seen from space - Hörmann, Christoph; Sihler, Holger; Platt, Ulrich (Atmospheric chemistry and physics, 2016)
The Rann of Kutch (India and Pakistan) is one of the largest salt deserts in the world. Being a so-called "seasonal salt marsh", it is regularly flooded during the Indian summer monsoon. We present 10 years of bromine monoxide (BrO) satellite observations by the Ozone Monitoring Instrument (OMI) over the Great and Little Rann of Kutch. OMI spectra were analysed using Differential Optical Absorption Spectroscopy (DOAS) and revealed recurring high BrO vertical column densities (VCDs) of up to 1.4 × 1014molec cm−2 during April/May, but no significantly enhanced column densities during the monsoon season (June-September). In the following winter months, the BrO VCDs are again slightly enhanced while the salty surface dries up. We investigate a possible correlation of enhanced reactive bromine concentrations with different meteorological parameters and find a strong relationship between incident UV radiation and the total BrO abundance. In contrast, the second Global Ozone Monitoring Instrument (GOME-2) shows about 4 times lower BrO VCDs over the Rann of Kutch than found by OMI and no clear seasonal cycle is observed. One reason for this finding might be the earlier local overpass time of GOME-2 compared to OMI (around 09:30 vs. 13:30LT), as the ambient conditions significantly differ for both satellite instruments at the time of the measurements. Further possible reasons are discussed and mainly attributed to instrumental issues. OMI additionally confirms the presence of enhanced BrO concentrations over the Dead Sea valley (Israel/Jordan), as suggested by former ground-based observations. The measurements indicate that the Rann of Kutch salt marsh is probably one of the strongest natural point sources of reactive bromine compounds outside the polar regions and is therefore supposed to have a significant impact on local and regional ozone chemistry.